Development of a novel, high-throughput imaged capillary isoelectric focusing-Western method to characterize charge heterogeneity of monoclonal antibody heavy and light chains - Gangadhar Dhulipala; Alanna Broszeit; Kun Lu; Nisha Palackal; Erica Pyles (mAbs)
Charge heterogeneity is one of the commonly monitored quality attributes in biotherapeutics. It can impact the stability, efficacy, and safety of products, but it can also affect the pharmacokinetics, binding affinity, and overall biological activity of the molecules. Given the substantial size and complexity of antibodies, subtle variations or specific modifications that result in charge heterogeneity might be concealed when mAbs are analyzed under native conditions. Two-dimensional gel electrophoresis has traditionally been used to characterize antibody heavy chain (HC) and light chain (LC) charge variants. The procedures, however, are laborious, and the method is only qualitative. ChromiCE was developed as an alternative approach to provide quantitative analysis, but the method is also labor intensive, requiring separation of the HC and LC by chromatography before imaged capillary isoelectric focusing (iCIEF) analysis. We thus developed a novel, automated high-throughput iCIEF-Western method to directly quantify the HC and LC charge variants with high sensitivity under denatured and reduced conditions. The HC and LC charge variants are selectively characterized using detection antibodies specific to the HC or LC. In addition, the reduced, denatured iCIEF-Western method allows for the analysis of up to 96 samples overnight, offering good precision and high throughput with minimal analyst hands-on time. Further, the developed method can be applied in different aspects of drug development, such as comparability, release or stability testing given its ability to provide identity, as well as qualitative and quantitative comparative analysis.